Adsorption of Cadmium, Chromium and Manganese by Natural Cellulose Materials - ชูจิตร กิตติพงษ์ (Progress in Applied Science and Technology, 2016)
The objective of this experiment is to study the adsorption of cadmium, chromium and manganese by using 12 natural cellulose materials with and without chemical modification process. The efficiency of metal adsorption was analyzed by atomic absorption spectrophotometry. The natural cellulose materials modified with chemical process showed better adsorption efficiency of these metals than the without modified materials. The cellulose of modified peanut shell gave the highest adsorption efficiency of cadmium as 64.07%. The cellulose of modified soybean shell gave the highest adsorption efficiency of chromium and manganese as 94.42 and 100%, respectively. The modified natural cellulose materials have potential for use to adsorb the cadmium, chromium and manganese in the waste water and in some production processes.